Subordinat Perempuan Dalam Aplikasi Percakapan Grup Whatsapp (Studi Kasus Penggunaan Sticker Sensual Di Grup Whatsapp) - Lina Wati; Muhammad Saifulloh (LUGAS Jurnal Komunikasi, 2020)
Technological developments open new spaces for interaction. Women are still issues in conversation today. Women are commodity from their bodies. This study discusses the use of whatsapp stickers that use photos of women's bodies, the use of these stickers is widely used in the application group whatsapp, this shows that women are still physically viewed, sexually exploited and placed subordinate in conversation. This type of research is a qualitative descriptive with case study research method, with the critical paradigm. Using interviews as a data collection technique, researchers interviewed group members who often used sensual female stickers to find out the background, motives and tried to uncover the practice of subordination of whatsapp group members who used female body sensual stickers. The results of this study show that the occupants of the group use sensual female body stickers as a joke, a medium of virtualization in the group. For men in the Whats app group, the use of a sensual female body as a conversation sticker, is a form of recognition of the beauty of the body and sexuality appeal of women. Subordinate practice in women occurs in whatsapp 19 Ers group conversations, when women's bodies in various sensual poses uses as mere joke objects.